Use of Innovative Methods in Modern Pedagogy - Alikhanovna, Ramazonova Mazgul (Research Parks Publishing LLC, 2023)
Serious changes related to the development of globalization, informatization, cosmonautics, robotics and artificial intelligence can be noted as new scientific results of the 21st century. This age can be called the age of digital technologies and modern knowledge. In the new century, the theory of school and education is undergoing serious changes. Now, we can hear criticism that the classrooms are not the same as they were a century ago, or even two centuries ago. Today's pedagogy is being manifested. Among them can be noted, the expansion of pedagogy, the ecological approach to teaching, the digital generation and the changes taking place in it, innovations in teaching. Today, are taking place the internationalization of education and the introduction of digital technologies.